Arts Management in the US and Russia: Pedagogical Aspects - Rich, J. Dennis; Shekova, Ekaterina L. (European Scientific Journal, ESJ, 2016)
The paper is about the pedagogical approaches in the arts administration programs in the US and Russia. For future cultural managers an understanding of culture and the arts forms one of the bases of intellectually engaged activity, enriches and sustains lifelong learning, and cultivates the capacity for empathetic and relational thinking. The cultural management pedagogy must offer students a rich array of educational instruction, programs, and opportunities across communication and arts disciplines.